Management of nitrobenzene poisoning in a resource-constrained setting: A case report - Subodh Bashyal; Manoj Karki; Sudhan Devkota; Aprajita Sharma; Binod Prasad Sah; Niraj Kumar Jaiswal; Bidhata Rayamajhi; Sabu Pokharel (Journal of Universal College of Medical Sciences, 2026)
INTRODUCTIONNitrobenzene poisoning is an uncommon but potentially fatal cause of acquired methemoglobinemia, particularly in agricultural regions. We report an 18-year-old male presenting with acute hypoxia, cyanosis, and refractory low oxygen saturation following unknown pesticide ingestion. Despite limited diagnostic resources, characteristic clinical features, chocolate-colored blood, and a marked saturation gap supported the diagnosis of methemoglobinemia. Prompt empirical treatment with oxygen, methylene blue, and ascorbic acid resulted in rapid recovery. This case highlights the importance of clinical recognition and early intervention in suspected nitrobenzene poisoning, especially in resource-limited settings.